2017
DOI: 10.18203/2394-6040.ijcmph20175346
|View full text |Cite
|
Sign up to set email alerts
|

A study of risk factors of hepatitis B infection among rural adult population of Patna, Bihar

Abstract: INTRODUCTIONGlobally 325 million people are HBsAg positive hence carriers of hepatitis B Virus (HBV).1 This is a public health challenge as majority of them have poor access to testing and treatment facilities. With a prevalence of 3 -4.2%, India is in the intermediate endemic zone but has around 40 million HBV carriers.2 Annually around 7,80,000 people die due to consequences of chronic HBV.2 Among those with infection, chances of becoming HBV carriers are 90% in infants, 30% in early childhood and upto 5% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
0
11
1
1
Order By: Relevance
“…[ 19 ] Additionally, in a case-control study conducted among a rural population in Phulwarisharif block of Patna, Bihar, to examine the risk factors for hepatitis B transmission in the rural area, 50% of the cases and 62% of the controls were aware of the hepatitis B disease, 40% in each group were aware of blood transfusion, and 20% about sexual route as a mode of spread. However, only 4% of the cases and 13% of the controls knew about the hepatitis B vaccination,[ 20 ] whereas in our study, 30% of the mothers knew about the sexual route and 16% about the blood transfusion. This is similar to a study conducted in three slums of Mumbai by Jha et al .…”
Section: Discussioncontrasting
confidence: 77%
“…[ 19 ] Additionally, in a case-control study conducted among a rural population in Phulwarisharif block of Patna, Bihar, to examine the risk factors for hepatitis B transmission in the rural area, 50% of the cases and 62% of the controls were aware of the hepatitis B disease, 40% in each group were aware of blood transfusion, and 20% about sexual route as a mode of spread. However, only 4% of the cases and 13% of the controls knew about the hepatitis B vaccination,[ 20 ] whereas in our study, 30% of the mothers knew about the sexual route and 16% about the blood transfusion. This is similar to a study conducted in three slums of Mumbai by Jha et al .…”
Section: Discussioncontrasting
confidence: 77%
“…This finding is similar to the unmatched case–control study conducted in rural areas of Patina, India, which showed that those who were unaware of transmission through sexual contact were more likely to contract hepatitis B virus infection as compared to participants having awareness of transmission through sexual contact. 20 This could be because infection with the hepatitis B virus can also be transmitted through semen and blood. Therefore, awareness of this can be the prerequisite for preventing the contraction of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the questions were taken from questionnaires from other studies to investigate risk factors of hepatitis B virus infection. 20 , 29 , 30 Data were collected through face-to-face interviews with patients by trained experienced health professionals using pre-tested and interviewer-structured questionnaires. They were interviewed by trained health workers at Ayder comprehensive specialized hospital about their socio-demography, healthcare service-related factors, behavioural factors and awareness of hepatitis B virus infection.…”
Section: Methodsmentioning
confidence: 99%
“…The results of a study in India showed that higher sero-positive HBsAg cases were found in adults with a history of migration. 14 Other studies have shown that the risk of sero-positive HBsAg is higher in pregnant women with a history of having their husbands working abroad.…”
Section: Original Articlementioning
confidence: 99%
“…Studies in Africa showed that a history of first-time sexual intercourse within the age <19 years in women 9-11 and having multiple sexual partners 9,10,12,13 increase the risk of HBV infection in pregnant women. In addition to sexual behavior, a study in India reported that the risk of HBV infection was higher among residents with a history of migration to find work, 14 whereas in Ethiopia and Turkey was higher among pregnant women who had permanent tattoos. 15,16 Another study in Kabul, Turkey showed that HBV infection was associated with injecting drug use.…”
Section: Introductionmentioning
confidence: 99%